2015
DOI: 10.1589/jpts.27.2091
|View full text |Cite
|
Sign up to set email alerts
|

Clinical physical therapists research activity reality and barriers to their utilizing research findings

Abstract: [Purpose] This research study was performed to investigate the barriers to using the research findings of physical therapists on evidence-based practice. [Subjects] The subjects of this research were physical therapists employed by hospitals that agreed to cooperate with the research in B city. [Methods] A questionnaire made up of 6 research items, 8 physical therapist items, 6 presentation items, and 8 setting items, for a total of 28 items, was distributed. The responses were scored so the higher result scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Education, training, and peer support may be key strategies for promoting EBP knowledge, skills, attitudes, and behavior (evidence seeking) . Other studies have reported that continued education facilitates critical evaluation among physiotherapists and that to promote physiotherapists' use of EBP, systematic implementation of new learning is needed, particularly learning that demonstrates the practical applications of research results . To understand how EBP is carried out and how decisions are made in daily practice, it is important to grasp how the concept of evidence is perceived, there is still a lack familiarity regarding its concepts and applications …”
Section: Introductionmentioning
confidence: 99%
“…Education, training, and peer support may be key strategies for promoting EBP knowledge, skills, attitudes, and behavior (evidence seeking) . Other studies have reported that continued education facilitates critical evaluation among physiotherapists and that to promote physiotherapists' use of EBP, systematic implementation of new learning is needed, particularly learning that demonstrates the practical applications of research results . To understand how EBP is carried out and how decisions are made in daily practice, it is important to grasp how the concept of evidence is perceived, there is still a lack familiarity regarding its concepts and applications …”
Section: Introductionmentioning
confidence: 99%
“…It was important to make the creation of local recommendations through small groups feasible. This is because the availability of local recommendations created via active participation of users is a strategy believed to improve use of EBP [3,24,[26][27][28]32,33]. Furthermore, when clinical questions were left unanswered by the COG, a research study was frequently initiated.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, education of therapists on the KT process and local recommendations was believed to have been key revisions as on‐going education is a strategy shown to improve the success of KT . Strategies utilized to educate our staff including in‐services and brief written summaries have been found to be effective .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations